Relationship Between Fast Food Eating Behaviour and Prevalence of Obesity in Children Aged 7-12 Years in Nganjuk, Indonesia - Divya Andini Yustanti (Ficco Public Health Journal, 2024)
Background: Obesity is a common problem among children today. Obesity can cause negative health effects. The habit of consuming fast food can increase various diseases such as hypertension, obesity and diabetes. Objective this study to determine the association of fast food consumption behavior with the incidence of obesity in school-aged children 7-12 years. Methods: This research design is an observational analytic survey with a cross-sectional approach. The sampling technique used Simple random sampling with a sample of 103 children. Results: Based on the results of the study there were 32% of students who were obese, respondents in the category of frequent fast food consumption 38.8% and the results of statistical tests showed that the p-value = 0.025 ≤ α 0.05 then Ha was accepted and Ho was rejected. Conclusion: There is a relationship between fast food consumption behavior and the incidence of obesity in school-age children aged 7-12 years at SD Negeri 1 Kutorejo. It is expected that students reduce the consumption of fast food that contains high sugar, salt, flour, and fat by consuming nutritious and balanced foods, and spending time in physical activity.